Methods for Characterizing Internal Stress in Amorphous Polymer Materials
Differential scanning calorimetry (DSC) characterizes the internal stress of amorphous polymer materials, solves the problem that the residual stress of amorphous polymer materials cannot be effectively characterized in the prior art, realizes efficient and rapid quantitative analysis, and optimizes the The molding process and mold design improve the quality of the product and the application pass rate.
Patent Information
- Application Number
- CN202110497121.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-07
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-05-07
AI Technical Summary
The prior art cannot effectively characterize the residual stress of amorphous polymer materials, and the existing methods are limited in application scope or the test results are difficult to quantify, so it is impossible to distinguish internal stresses at different depth positions.
Differential scanning calorimetry (DSC) is used to measure the internal stress of amorphous polymer materials. By recording the difference in the differential scanning calorimetry curve of the sample at different temperature rates, the internal stress value is calculated, and the glass transition temperature and peak area are used. Perform analysis and quantitatively characterize internal stress.
An efficient and fast method is provided to characterize residual stresses of amorphous polymer materials, helping to optimize molding processes and mold designs, and improving product quality and application pass rate.
Smart Images

Figure CN115307798B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material processing, and in particular to a method for characterizing the internal stress of an amorphous polymer material. Background Art
[0002] Polymer materials are increasingly being used in production and life. The good processing properties and insulation properties of polymer materials make them suitable for most applications. At the same time, due to the limitations of the structural characteristics of polymer materials themselves, residual stress will inevitably exist in the products during the molding process of polymer materials. Residual stress will not only cause quality problems such as deformation and cracking of products, but in most cases, the existence of residual stress will shorten the life of the products.
[0003] Therefore, it is necessary to control the residual stress in polymer products. The commonly used methods are to reduce the residual stress by optimizing the molding process such as injection molding or extrusion, optimizing the molding mold, etc. on the one hand; and to eliminate the residual stress by heat treating the product on the other hand. The first method has the problem of high technical difficulty and difficulty in characterizing the residual stress; the second method increases the production cost and is not suitable for products such as high gloss products. At the same time, the product will deform during the heat treatment process. Therefore, the best way to control the residual stress of polymer products is to optimize the parameters in the processing process and reduce the magnitude of the residual stress. Therefore, the method of evaluating the magnitude of the residual stress of polymer products has become the key to the technology.
[0004] There are currently few methods for evaluating residual stress in polymer materials, which are as follows:
[0005] The patent "Method and device for measuring internal stress of amorphous transparent materials" (CN201810540405.2) discloses a method for measuring internal stress of amorphous transparent materials. Polarized light is applied to the measurement area of the test piece, the optical path difference between the birefringent polarized light generated by the polarized light on the test piece is obtained, and the internal stress value of the measurement area is obtained based on the correspondence between the optical path difference and the internal stress value. This method has good accuracy, but is limited to transparent materials, and shape factors such as the transmittance and thickness of the material will affect the test results.
[0006] The patent "A method for testing the internal stress of a film" (CN201810062607.0) heats the film sample to be tested to a preset temperature at a constant heating rate, and obtains the maximum shrinkage rate of the film sample to be tested during the heating process to characterize the internal stress of the film sample to be tested. This technology is limited to film materials, and it is difficult to measure the length of the film after shrinkage and deformation, resulting in inaccurate test data.
[0007] The patent "Injection molding polymer macromolecular orientation dynamic detection system and detection method thereof" (CN201810464872.1) provides a technology for injection molding macromolecular orientation detection of translucent polymer materials. The technology test system includes a molding module, a light source module, and an online monitoring module. The injection molding machine performs injection molding on the window visualization test mold; the incident light source can be divided into a reference light source and an interference light source by a spectroscope, and the interference light source enters the mold cavity for dynamic imaging. The holographic dry plate, CCD high-speed camera, etc. are installed on the lower side of the moving mold to record the instantaneous morphology of the polymer filling process, and then the relevant data is processed by the data processing system, with strong contrast and reliability; the temperature and pressure integrated sensor is arranged on the inner wall of the mold cavity, which can feedback the cavity temperature and stress distribution in real time, and dynamically adjust the cavity temperature and stress distribution with high accuracy. This technology is suitable for dynamic tracking during the injection molding process, but it is limited to transparent materials.
[0008] The patent "An ultrasonic Lamb wave device and method for measuring the internal stress of plastic thin plate products" (CN201510221488.5) uses the detection of Lamb wave amplitude to achieve quantitative measurement of the internal stress distribution of plastic thin plate products. The patent "Real-time detection method for internal stress distribution during injection compression molding of transparent products" (CN201310514990.6) uses a high-speed camera to take real-time pictures of the response of surface polarized light during the molding process of the product under polarized light, and calculates the residual stress under the process parameters. The patent "Plastic product internal stress immersion tester" (CN201410541114.7) uses the penetration and diffusion of solvents to accelerate the effect of internal stress, and judge the magnitude of internal stress by the degree of cracking of the material.
[0009] However, the above technologies have limitations such as limited application scope (mainly for transparent materials), difficulty in quantifying test results (solvent immersion and other tests), and inability to distinguish internal stress at different depths of the workpiece (ultrasonic Lamb wave measurement method). Based on the above reasons, it is necessary to provide a residual stress characterization method suitable for amorphous polymer materials. Summary of the invention
[0010] The main purpose of the present invention is to provide a method for characterizing the internal stress of an amorphous polymer material, so as to solve the problem that the residual stress of an amorphous polymer material cannot be effectively characterized in the prior art.
[0011] To achieve the above-mentioned purpose, according to one aspect of the present invention, a method for characterizing the internal stress of an amorphous polymer material is provided, which comprises the following steps: sampling: taking a sample of the amorphous polymer material to be tested; differential scanning calorimetry measurement: placing the sample in an aluminum crucible of a differential scanning calorimeter, covering it with an aluminum upper cover, and then heating it from room temperature to a target temperature at a first heating rate, and recording a differential scanning calorimetry curve of the first heating process; then, cooling the sample to room temperature; secondly, heating the sample from room temperature to a target temperature again at a second heating rate, and recording a differential scanning calorimetry curve of the second heating process; wherein the second heating rate is the same as the first heating rate; the target temperature is 50 to 150° C. below the thermal decomposition temperature of the amorphous polymer material to be tested, or is the processing and molding temperature of the amorphous polymer material to be tested; analyzing the internal stress results: taking the differential scanning calorimetry curve of the second heating process as a reference, comparing the differential scanning calorimetry curve of the first heating process with the difference therebetween, the greater the difference, the greater the internal stress of the amorphous polymer material to be tested.
[0012] Furthermore, the step of analyzing the internal stress results includes: taking the first glass transition temperature on the differential scanning calorimetry curve of the second heating process as a reference, selecting a temperature 10 to 50°C lower than the reference temperature, preferably 30°C lower than the reference temperature as the starting point temperature; moving the differential scanning calorimetry curve of the first heating process along the ordinate direction so that it intersects with the differential scanning calorimetry curve of the second heating process at the starting point temperature, and recording the intersection as the starting point; at this time, when the differential scanning calorimetry curve of the first heating process and the differential scanning calorimetry curve of the second heating process are at the same temperature, There is an intersection point near the target temperature, and the intersection point is taken as the end point. When the differential scanning calorimetry curve of the first heating process and the differential scanning calorimetry curve of the second heating process do not intersect near the target temperature, the midpoint of the vertical coordinate connecting the two at the target temperature is taken as the end point; the starting point and the end point are connected by a straight line, and the straight line is taken as the baseline; the peak area of the differential scanning calorimetry curve of the second heating process relative to the baseline is calculated as the baseline area S1; with the baseline as a reference, the peak area of the peak of the differential scanning calorimetry curve of the first heating process located above the baseline is recorded as S in , where n represents the sequence number of the peak, and n ≥ 1; the peak area of the peak below the baseline in the differential scanning calorimetry curve of the first heating process is recorded as S jm , where m represents the peak sequence number, and m≥1; the value of internal stress is calculated using the following formula: δ 内应力 =(S1-∑S in +∑S jm ) / S1.
[0013] Furthermore, the target temperature is recorded as T, and the temperature close to the target temperature is within a temperature range of ≤T and ≥(T-50).
[0014] Furthermore, the first heating rate is 2 to 50°C / min, preferably 10°C / min; the cooling rate during the cooling process is 2 to 100°C / min, preferably the cooling rate is the same as the first heating rate.
[0015] Furthermore, the amorphous polymer material to be tested is selected from unprocessed polymer raw materials, extrusion molded products or injection molded products.
[0016] Furthermore, when the amorphous polymer material to be tested is an extrusion molded product or an injection molded product, the sampling process includes: performing the sampling process on the molded product mechanically, or performing the sampling process by separating the molded product with a heated blade.
[0017] Furthermore, during the sampling process, the temperature rise of the sampled part is controlled to be less than 20°C, preferably less than 10°C.
[0018] Furthermore, the thickness of the sample is less than 5 mm and greater than 0.2 mm; preferably, the thickness of the sample is less than 2 mm and greater than 0.2 mm; and the weight of the sample is 1 to 50 mg.
[0019] Furthermore, the differential scanning calorimetry measurement process is carried out under nitrogen protection, and the nitrogen flow rate is 10 to 80 ml / min, preferably 50 ml / min.
[0020] Furthermore, the amorphous polymer material to be tested is ABS resin, SAN resin, PS resin, HIPS resin or PC resin.
[0021] The present invention provides a method for characterizing the internal stress of an amorphous polymer material. The method uses differential scanning calorimetry (DSC) to characterize the magnitude of the internal residual stress of an amorphous polymer material based on the molecular structure characteristics of the amorphous polymer material. The method is an efficient and rapid method for characterizing the residual stress of an amorphous polymer material, and provides a basis for optimizing the molding process and mold design of an amorphous polymer material. By testing the magnitude of the residual stress, the molding parameters are optimized in a targeted manner, and then a product with excellent quality is obtained, thereby improving the qualified rate of the processing and molding of the amorphous polymer material in the application process of electroplating, heat resistance, creep resistance, chemical resistance and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0023] Figure 1 A typical DSC curve of ABS resin at 50-440°C is shown;
[0024] Figure 2A typical DSC curve of ABS injection molded parts is shown;
[0025] Figure 3 shows a typical DSC curve of ABS granular resin sample;
[0026] Figure 4 The figure shows the two DSC temperature rise curves in Example 1 of the present invention after being corrected;
[0027] Figure 5 A heat absorption area curve of the second temperature rise curve in Example 1 of the present invention is shown;
[0028] Figure 6 The heat absorption and heat release area curve of the first heating curve in Example 1 of the present invention is shown;
[0029] Figure 7 The schematic diagram of the structure of the injection molded product spline in Example 2 of the present invention is shown;
[0030] Figure 8 The figure shows two corrected DSC curves of sample 1# in Example 2 of the present invention;
[0031] Fig. 9 The figure shows two corrected DSC curves of sample 2# in Example 2 of the present invention;
[0032] Fig.10 A photograph of a SAN resin injection molded product strip having vacuum bubbles in Example 3 of the present invention is shown;
[0033] Fig.11 The figure shows two corrected DSC curves of sample 1# in Example 3 of the present invention;
[0034] Fig.12 The figure shows two corrected DSC curves of sample 2# in Example 3 of the present invention;
[0035] Fig.13 The figure shows two corrected DSC curves of the sample with an injection speed of 20 mm / s in Example 4 of the present invention;
[0036] Fig.14 The figure shows two corrected DSC curves of the sample with an injection speed of 120 mm / s in Example 4 of the present invention;
[0037] Fig.15 The corrected DSC curves of the second and third heating of the SAN resin powder of Example 5 of the present invention are shown. DETAILED DESCRIPTION
[0038] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0039] As described in the background technology section, the residual stress of amorphous polymer materials cannot be effectively characterized in the prior art. In order to solve this problem, the present invention provides a method for characterizing the internal stress of an amorphous polymer material, which comprises the following steps: sampling: taking a sample of the amorphous polymer material to be tested; differential scanning calorimetry measurement: placing the sample in an aluminum crucible of a differential scanning calorimeter, covering it with an aluminum upper cover, and then heating it from room temperature to a target temperature at a first heating rate, and recording a differential scanning calorimetry curve of the first heating process; then, cooling the sample to room temperature; secondly, heating the sample from room temperature (20-50°C) to a target temperature again at a second heating rate, and recording a differential scanning calorimetry curve of the second heating process; wherein the second heating rate is the same as the first heating rate; the target temperature is 50-150°C below the thermal decomposition temperature of the amorphous polymer material to be tested, or is the processing and molding temperature of the amorphous polymer material to be tested; analyzing the internal stress result: taking the differential scanning calorimetry curve of the second heating process as a reference, comparing the differential scanning calorimetry curve of the first heating process with the difference therebetween, and the greater the difference, the greater the internal stress of the amorphous polymer material to be tested.
[0040] DSC (Differential Scanning Calorimetry) is an important method for detecting the molecular structure, composition and thermal behavior of polymer materials. As the temperature rises, the volume of the polymer material increases, the distance between the molecular chains increases, and the chain segments, end groups and other structures on the molecular chain absorb heat and begin to move, forming an obvious endothermic peak on the DSC temperature rise curve. As the temperature continues to rise, the polymer material gradually enters the viscous flow state from the highly elastic state until the polymer material decomposes under high temperature conditions, and the decomposition will absorb more heat.
[0041] Taking ABS resin as an example, its DSC curve at 50-440°C under nitrogen conditions is as follows: Figure 1 As shown. It can be seen that the sample has been absorbing heat before 350℃, and the glass transition endothermic peak appears at 114℃. After 180℃, the ABS resin gradually becomes a viscous flow state. Since the ABS resin does not crystallize, there is no melting endothermic peak. After 350℃, a small amount of heat release occurs (it may be that the nitrogen purity is not enough, and the polymer material produces a small amount of oxidation heat release), and then a large number of decomposition endothermic peaks appear (after 380℃). In the process of heating from 50℃ to 440℃, the mobility of each molecular structure in the polymer gradually increases, and the movement of different molecular structures shows different thermal effects, which is reflected in the DSC curve.
[0042] The molecular chain of amorphous polymer materials is a random coil structure, but during the polymer molding process, the coil structure will be destroyed, the molecular chain as a whole will be stretched, or part of the molecular chain will be stretched. After cooling, the molecular chain or chain segment that has not recovered to the random coil structure has a tendency to recover, thus forming residual stress.
[0043] Taking ABS injection molded parts as an example, its DSC test curve is shown in Figure 2 Curve 1 is the DSC curve of the first heating process of the sample. The DSC curve is abnormal due to the internal stress in the sample. Curve 2 is the glass transition peak of the test material after the same sample is cooled (heat treated) after the first heating and the internal stress is eliminated. There is a significant difference between curve 1 and curve 2. The internal stress of curve 1 is released obviously near the glass transition temperature, and the stress release process of curve 1 is relaxed after the temperature is higher than the glass transition temperature. Figure 2 Curve 2 is a typical DSC curve of ABS resin. As the temperature rises, a glass transition peak appears in the range of 100-140°C, and the curve is basically smooth without peaks at other temperatures. Compared with curve 2, curve 1 is different, showing the internal stress contained in the sample. Near the glass transition temperature, due to the high enough temperature, the oriented or stretched polymer chain segments and other structures begin to move. The chain segments and other structures in curve 2 absorb heat at this temperature and begin to move passively, showing an obvious endothermic peak, while in curve 1, due to the stretching of the chain segments (the reason for the generation of internal stress), when the temperature rises and the intermolecular space meets the conditions for the movement of the chain segments, the chain segments actively move (recover) under the action of internal stress, generating heat release. And the heat release (exothermic peak area) is proportional to the degree of stretching of the chain segments (the magnitude of internal stress).
[0044] As the temperature continues to rise, the polymer chains gain more space and energy, and meet the conditions for molecular chain movement. In curve 2, there is no force between the molecular chains, and they move freely. As the temperature rises, they absorb heat at a constant rate. However, due to the existence of internal stress, the molecular chains in curve 1 are stretched, and the molecular chains actively move, which also reflects the phenomenon of heat release. The amount of heat released is proportional to the magnitude of the internal stress between the molecular chains.
[0045] Based on the above analysis and research, the present invention provides the above method for characterizing the internal stress of amorphous polymer materials. According to the molecular structure characteristics of amorphous polymer materials, DSC is used to characterize the magnitude of the internal residual stress of amorphous polymer materials. It is an efficient and rapid method for characterizing the residual stress of amorphous polymer materials, and provides a basis for optimizing the molding process and mold design of amorphous polymer materials. By testing the magnitude of residual stress, the molding parameters are optimized in a targeted manner, and then products with excellent quality are obtained, which improves the qualified rate of amorphous polymer materials in the process of processing and molding in the fields of electroplating, heat resistance, creep resistance, and chemical resistance.
[0046] In a preferred embodiment, the step of analyzing the internal stress results includes: taking the first glass transition temperature on the differential scanning calorimetry curve of the second heating process as a reference, selecting a temperature 10 to 50°C lower than the reference temperature, preferably 30°C lower than the reference temperature as the starting temperature; moving the differential scanning calorimetry curve of the first heating process along the ordinate direction so that it intersects with the differential scanning calorimetry curve of the second heating process at the starting temperature, and recording the intersection as the starting point; at this time, when the differential scanning calorimetry curve of the first heating process intersects with the differential scanning calorimetry curve of the second heating process The thermal curve has an intersection near the target temperature, and the intersection is taken as the end point. When the differential scanning calorimetry curve of the first heating process and the differential scanning calorimetry curve of the second heating process do not intersect near the target temperature, the midpoint of the vertical coordinate connecting the two at the target temperature is taken as the end point; the starting point and the end point are connected by a straight line, and the straight line is taken as the baseline; the peak area of the differential scanning calorimetry curve of the second heating process relative to the baseline is calculated as the baseline area S1; with the baseline as a reference, the peak area of the peak of the differential scanning calorimetry curve of the first heating process located above the baseline is recorded as S in , where n represents the sequence number of the peak, and n ≥ 1; the peak area of the peak below the baseline in the differential scanning calorimetry curve of the first heating process is recorded as S jm , where m represents the peak sequence number, and m≥1; the value of internal stress is calculated using the following formula: δ 内应力 =(S1-∑S in +∑S jm ) / S1.
[0047] It should be noted that although the two DSC tests were controlled to be carried out at the same heating rate, the same heating starting point and the same heating end point, the influence of the sample shape cannot be eliminated. During the first heating process, the contact between the sample and the aluminum crucible is surface contact, but due to the influence of the surface flatness of the sample, it is actually point and line contact. As the temperature rises, the material enters a viscous flow state, and the sample deforms slightly under the action of gravity, etc., and the contact area between the sample and the aluminum crucible increases. This change affects the test results and needs to be corrected. Figure 3As shown, it is the DSC curve of the granular ABS resin sample, wherein curve 1 is the first heating curve, and curve 2 is the DSC curve of the sample after heat treatment. After 220°C, the heat absorption rate of curve 1 is higher than that of curve 2. This is due to the difference caused by the change in sample shape and needs to be corrected. Therefore, the present invention uses the above-mentioned method of analyzing the internal stress results, selects the starting temperature based on the first glass transition temperature, moves the DSC curve of the first heating process in the longitudinal direction so that the two curves intersect at the starting temperature, and then selects the end point. Finally, the connecting line between the starting point and the end point is used as the reference line to correct the two DSC curves, which can make the internal stress analysis results more reliable. Preferably, the target temperature is recorded as T, and the temperature range close to the target temperature is ≤T and ≥(T-50).
[0048] The object of the above characterization method is amorphous polymer materials, including but not limited to the amorphous polymer materials to be tested are selected from unprocessed polymer raw materials, extrusion molded products or injection molded products. The amorphous polymer materials used include but are not limited to ABS resin, SAN resin, PS resin, HIPS resin or PC resin, etc.
[0049] When the amorphous polymer material to be tested is an extruded product or an injection molded product, the preferred sampling process includes: performing a sampling process on the molded part by mechanical means, or performing a sampling process by separating the molded part using a heated blade. In the specific implementation process, one or more sampling positions can be selected according to the test needs. If the internal stress of the part under different molding processes is compared, it is necessary to ensure that the sampling position is the same each time. In order to avoid the release of residual stress of the material as much as possible during the sampling process, thereby making the characterization more reliable, in a preferred embodiment, during the above sampling process, the temperature rise of the sampled part is controlled to be less than 20°C, preferably less than 10°C.
[0050] Specifically, a relatively large sample can be cut from the workpiece first, and then polished to the required size on sandpaper with a mesh size of 1000 or above. The speed of the polishing process is controlled to avoid the sample temperature rising by more than 20°C. Each time the sample is prepared, the size, shape and quality of the sample are basically the same. In order to avoid interference with the test results as much as possible, it is more preferred that the thickness of the sample is less than 5mm and greater than 0.2mm; the thickness of the sample is preferably less than 2mm and greater than 0.2mm; the weight of the sample is 1-50mg.
[0051] In a preferred embodiment, the first heating rate is 2 to 50°C / min, preferably 10°C / min; the cooling rate during the cooling process is 2 to 100°C / min, preferably the cooling rate is the same as the first heating rate. More preferably, after cooling, the second heating is performed after the constant temperature is maintained for 1 to 5 minutes. Preferably, the differential scanning calorimetry measurement process is carried out under nitrogen protection, and the nitrogen flow rate is 10 to 80 ml / min, preferably 50 ml / min. In this way, the test conditions such as the heating rate and the nitrogen rate are fixed, and the moisture in the sample will evaporate completely during the first heating process. For most random polymers such as ABS resin, the moisture basically evaporates before the glass transition, so the moisture has little effect on the test results. However, the residual monomers will gasify at a higher temperature, affecting the test results, but the residual stress monomer content in general polymer materials is very low, which has little effect on the test results. Therefore, the sample quality can be regarded as consistent and unchanged during the test process. Since the upper limit of the test temperature is much lower than the decomposition temperature of the material, there is basically no chemical change in the polymer material during the test.
[0052] During the test, the prepared sample is placed in an aluminum crucible, covered with an aluminum cover, and compacted (in the process of compacting the cover, care should be taken to avoid applying too much stress to the sample. If the sample size is large, the cover can be omitted to avoid stress during compaction), and then the heating process is carried out.
[0053] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0054] Embodiment 1:
[0055] Calculation of internal stress of the same ABS resin particles.
[0056] One ABS resin particle (Φ3×3mm, obtained by extrusion, water bath cooling, and pelletizing) (22.7mg) was selected and placed in a DSC, heated from 50°C to 250°C at 10°C / min, and then cooled from 250°C to 50°C at 10°C / min. After keeping the temperature constant for 2 minutes, the temperature was raised from 50°C to 250°C at 10°C / min, and two DSC temperature rise curves were obtained successively.
[0057] Move the DSC curve after the first heating so that the two curves intersect at the starting point temperature 30°C before the first glass transition temperature of the DSC curve after the second heating. The two curves also have an intersection at the processing temperature of 220°C. Connect the two intersection points of the two curves to generate a baseline (such as Figure 4 shown). Figure 4The first temperature rise curve absorbs heat and rises near 220℃, which is consistent with the analysis of the effect of particle shape change on the DSC curve. Therefore, the intersection of the two curves near 220℃ is taken as the end point.
[0058] Based on the baseline, calculate the heat absorption area of the second heating curve, such as Figure 5 . By calculation, S1=65.87.
[0059] Based on the baseline, calculate the heat absorption and heat release areas of the first heating curve, such as Figure 6 . Where S i1 is the heat absorption area, S j1 , S j2 is the heat release area. By calculating S j1 =1.10, S i1 =12.97, S j2 =16.80.
[0060] Internal stress δ = (S1-S i1 +S j1 +S j2 ) / S1=(65.87-12.97+1.10+16.80) / 65.87=1.08
[0061] The molding process of ABS resin particles is affected by the temperature of cooling water. The particle surface is cooled and shaped first, and the internal melt is gradually cooled, forming shrinkage stress. In extreme cases, shrinkage bubbles will be generated. Therefore, there is a certain internal stress inside the ABS resin particles, which shows that the above characterization results are relatively reliable.
[0062] Example 2
[0063] Internal stress test at different locations on the same ABS resin injection molded part.
[0064] like Figure 7 As shown in the figure, two points were taken from the same injection molded spline (80×10×4mm) at a distance of 10mm from the gate. Point 1# was located at the edge of the spline, and point 2# was parallel to point 1# but not adjacent to point 1# and was located in the middle of the spline. 4.4×1.8×1.9mm samples were taken from points 1# and 2# with a saw blade (grinded to the same size with 1200-grit sandpaper, and the temperature rise was controlled to be less than 10°C during the process), and the sample mass was about 14mg.
[0065] There are two reasons why injection molded samples generate internal stress. One is the shear caused by the injection speed, which leads to orientation stress; the other is the shrinkage stress caused by molecular shrinkage. Orientation stress is mostly generated on the surface of the part or where the shear stress is relatively large, while shrinkage stress is mostly generated inside the part. The main difference between the 1# and 2# points in this test is that the six surfaces of the 1# point include two surfaces of the original part, while the 2# point only includes one surface.
[0066] DSC test process: the temperature was raised from 50°C to 250°C at 10°C / min, and then lowered from 250°C to 50°C at 10°C / min. After 2 minutes of constant temperature, the temperature was raised from 50°C to 250°C at 10°C / min. The curve processing method was the same as that in Example 1. The DSC curves and baselines of sample 1# and sample 2# after processing were as follows: Figure 8 and Fig. 9 shown.
[0067] The calculated internal stress of sample 1 is δ = (S1-S i1 +S j1 +S j2 ) / S1=(32.15-0.95+14.78+54.39) / 32.15=3.12
[0068] The calculated internal stress of sample 2# is δ = (S1-S i1 +S j1 +S j2 ) / S1=(57.60-41.33+1.47+0.57) / 57.60=0.32
[0069] By comparison, it is found that the residual stress at the edges and corners of the workpiece is greater, which is consistent with the actual experience and theoretical analysis results.
[0070] Example 3
[0071] Internal stress test at different locations on the same SAN resin injection molded sample.
[0072] Adjusting the injection molding process and reducing the injection volume resulted in under-injection of the SAN resin injection molded samples. Due to the lack of pressure holding, the samples shrank severely, and vacuum bubbles appeared in some locations due to shrinkage (see Fig.10 ).
[0073] Samples were taken from the above injection molded samples, sample #1 was taken from the area with bubbles, and sample #2 was taken from the area without bubbles. The sampling method was the same as in Example 2.
[0074] DSC test process: the temperature was raised from 50°C to 250°C at 10°C / min, and then lowered from 250°C to 50°C at 10°C / min. After 2 minutes of constant temperature, the temperature was raised from 50°C to 250°C at 10°C / min. The curve processing method was the same as that in Example 1. The DSC curves and baselines of sample 1# and sample 2# after processing were as follows: Fig.11 and Fig.12 shown.
[0075] The internal stress of sample 1# is calculated as δ = (S1-S i1 +S j1 +S j2) / S1=(44.92-1.93+3.77+70.98) / 44.92=2.62
[0076] The internal stress of sample 2# was calculated to be δ = (S1-S i1 +S j1 ) / S1=(32.31-7.62+8.64) / 32.31=1.03
[0077] The lack of pressure holding inside the entire SAN resin injection molded part leads to relatively large shrinkage stress. By comparison, it is found that the residual stress in the resin at the location where the vacuum bubble is formed is larger, which is consistent with the characterization results.
[0078] Example 4
[0079] Test of internal stress changes under different injection molding conditions.
[0080] Injection molding of the same ABS resin, adjust the injection speed, and keep other molding conditions unchanged. Take two samples before and after the injection speed change, and use a saw blade to take samples at the same position of the sample. The sample size is 3×2.2×2mm, about 10.5mg.
[0081] DSC test process: the temperature was raised from 50°C to 250°C at 10°C / min, and then the temperature was lowered from 250°C to 50°C at 10°C / min. After 2 minutes of constant temperature, the temperature was raised from 50°C to 250°C at 10°C / min. The curve processing method was the same as that in Example 1. The DSC curve of the sample with an injection speed of 20 mm / s after correction is shown in Fig. Fig.13 The corrected DSC curve of the sample with an injection speed of 120 mm / s is shown in Fig.14 .
[0082] The internal stress of the sample at an injection speed of 20 mm / s is δ = (S1-S i1 +S j1 ) / S1=(11.05-11.28+6.59) / 11.05=0.58
[0083] The internal stress of the sample at an injection speed of 120 mm / s is δ = (S1-S i1 +S j1 ) / S1=(26.10-4.44+58.34) / 26.10=3.07
[0084] Increasing the injection speed leads to an increase in the residual stress of the material, which is consistent with the result that the internal stress increases from 0.58 to 3.07. This data can be used to guide the optimization of the injection molding process.
[0085] Example 5
[0086] Internal stress test of heat-treated SAN resin.
[0087] Take 5 mg of SAN resin powder, place it in a DSC, heat it from 50°C to 200°C at a heating rate of 10°C / min, and then cool it from 200°C to 50°C at 10°C / min (the first heating here is equivalent to heat treatment of the sample). After 5 minutes of constant temperature, heat it for the second time (equivalent to the first heating of the heat-treated sample), heat it from 50°C to 200°C at a heating rate of 10°C / min, and then cool it from 200°C to 50°C at 10°C / min. After 5 minutes of constant temperature, heat it for the third time (equivalent to the second heating of the heat-treated sample), heat it from 50°C to 200°C at a heating rate of 10°C / min, and then cool it from 200°C to 50°C at 10°C / min. The DSC curves of the second and third heating times are corrected as shown below. Fig.15 As shown (for a clearer presentation, the baseline and the third heating curve are moved up, and the baseline and the second heating curve are moved down, which does not affect the calculation).
[0088] The calculated internal stress of SAN resin after heat treatment is δ = (S1-S i1 ) / S1=(26.00-24.97) / 26.00=0.04
[0089] The residual stress in SAN resin after heat treatment is very small, which is consistent with the actual situation.
[0090] Through the above data analysis, the internal stress of the material can be quantitatively analyzed by DSC, thereby guiding the optimization of the molding process.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for characterizing the internal stress of an amorphous polymer material, characterized in that: The following steps are involved: Sampling: Take samples of the amorphous polymer material to be tested; Differential scanning calorimetry measurement: the sample is placed in an aluminum crucible of a differential scanning calorimeter, covered with an aluminum upper cover, and then heated from room temperature to a target temperature at a first heating rate, and a differential scanning calorimetry curve of the first heating process is recorded; then, the sample is cooled to the room temperature; secondly, the sample is heated from the room temperature to the target temperature again at a second heating rate, and a differential scanning calorimetry curve of the second heating process is recorded; wherein the second heating rate is the same as the first heating rate; the target temperature is 50 to 150°C below the thermal decomposition temperature of the amorphous polymer material to be tested, or is the processing and molding temperature of the amorphous polymer material to be tested; Analysis of internal stress results: Taking the differential scanning calorimetry curve of the second heating process as a reference, the differential scanning calorimetry curve of the first heating process is compared with the differential scanning calorimetry curve. The greater the difference, the greater the internal stress of the amorphous polymer material to be tested.
2. The method for characterizing internal stress of amorphous polymer materials according to claim 1, characterized in that: The step of analyzing the internal stress results comprises: Taking the first glass transition temperature on the differential scanning calorimetry curve of the second heating process as a reference, a temperature 10 to 50° C. lower than the reference temperature is selected as a starting point temperature; Move the differential scanning calorimetry curve of the first heating process along the ordinate direction so that it intersects with the differential scanning calorimetry curve of the second heating process at the starting point temperature, and record the intersection as the starting point; at this time, when the differential scanning calorimetry curve of the first heating process and the differential scanning calorimetry curve of the second heating process have an intersection near the target temperature, take it as the end point; when the differential scanning calorimetry curve of the first heating process and the differential scanning calorimetry curve of the second heating process do not intersect near the target temperature, take the midpoint of the ordinate connecting line of the two at the target temperature as the end point; connect the starting point and the end point with a straight line, and take the straight line as the reference line; Calculating the peak area of the differential scanning calorimetry curve of the second heating process relative to the baseline as the baseline area S1; Taking the baseline as a reference, the peak area of the peak above the baseline in the differential scanning calorimetry curve of the first heating process is recorded as S in , where n represents the sequence number of the peak, and n≥1; the peak area of the peak below the baseline in the differential scanning calorimetry curve of the first heating process is recorded as S jm , where m represents the sequence number of the peak, and m≥1; The value of the internal stress is calculated using the following formula: 内应力 =(S1-∑S in +∑S jm ) / S1.
3. The method for characterizing internal stress of amorphous polymer materials according to claim 2, characterized in that: A temperature 30° C. lower than the reference temperature is selected as the starting point temperature.
4. The method for characterizing internal stress of amorphous polymer materials according to claim 2, characterized in that: The target temperature is recorded as T, and the temperature close to the target temperature is within a temperature range of ≤T and ≥(T-50).
5. The method for characterizing the internal stress of an amorphous polymer material according to any one of claims 1 to 4, characterized in that: The first heating rate is 2-50°C / min; the cooling rate during the cooling process is 2-100°C / min.
6. The method for characterizing internal stress of amorphous polymer materials according to claim 5, characterized in that: The first heating rate is 10°C / min.
7. The method for characterizing internal stress of amorphous polymer materials according to claim 5, characterized in that: The temperature reduction rate is the same as the first temperature increase rate.
8. The method for characterizing the internal stress of an amorphous polymer material according to any one of claims 1 to 4, characterized in that: The amorphous polymer material to be tested is selected from unprocessed polymer raw materials, extrusion molded products or injection molded products.
9. The method for characterizing internal stress of amorphous polymer materials according to claim 8, characterized in that: When the amorphous polymer material to be tested is the extrusion molded product or the injection molded product, the sampling process includes: The sampling process is performed on the molded product by mechanical means, or by separating the molded product with a heated blade.
10. The method for characterizing internal stress of amorphous polymer materials according to claim 9, characterized in that: During the sampling process, the temperature rise of the sampled part is controlled to be less than 20°C.
11. The method for characterizing internal stress of amorphous polymer materials according to claim 10, characterized in that: During the sampling process, the temperature rise of the sampled part is controlled to be less than 10°C.
12. The method for characterizing internal stress of amorphous polymer materials according to claim 9, characterized in that: The thickness of the sample is less than 5 mm and greater than 0.2 mm; the weight of the sample is 1-50 mg.
13. The method for characterizing internal stress of amorphous polymer materials according to claim 12, characterized in that: The thickness of the sample is less than 2 mm and greater than 0.2 mm.
14. The method for characterizing the internal stress of an amorphous polymer material according to any one of claims 1 to 4, characterized in that: The differential scanning calorimetry measurement process was carried out under nitrogen protection, and the nitrogen flow rate was 10-80 ml / min.
15. The method for characterizing internal stress of amorphous polymer materials according to claim 14, characterized in that: The nitrogen flow rate is 50 ml / min.
16. The method for characterizing the internal stress of an amorphous polymer material according to any one of claims 1 to 4, characterized in that: The amorphous polymer material to be tested is ABS resin, SAN resin, PS resin, HIPS resin or PC resin.
Citation Information
Patent Citations
Real-time detection method for internal stress distribution in transparent product injection compression molding process
CN103552225A
Internal stress soaking testing machine of plastic product
CN104228013A
Device and method for measuring internal stress of plastic sheet products on basis of ultrasonic lamb waves
CN104807570A
Test method of internal stress of thin film
CN108445037A
Injection molding polymer macromolecular orientation dynamic detection system and detection method thereof
CN108705751A